Abiotic Measurements from a three-month mesocosm experiment on Sylt, Germany, in 2023 - Mehler, Knut; Steinmann, Anna; Rick, Johannes J (PANGAEA, 2025)
This dataset comprises abiotic parameters measured during a mesocosm experiment using the AWI Sylt Outdoor Mesocosm (AWISOM) facility conducted on the island of Sylt, Germany, in 2023. The experiment spanned approximately three months, beginning on 16 March 2023. A total of 12 mesocosms were deployed, with six mesocosms assigned to each of two temperature treatments: in situ ambient, and ambient +3.0 °C. Water samples were collected from each mesocosm at a depth of 0.1 m on 103 discrete sampling days. The sampling frequency varied by parameter, with some variables measured daily and others once or several times per week. Recorded parameters include water temperature, dissolved oxygen, pH (HBS scale), conductivity, chlorophyll a, total alkalinity, and concentrations of dissolved inorganic nutrients (phosphate, nitrate, nitrite, ammonium, and silicate). Measurements were carried out using multiparameter probes and laboratory methods. The dataset provides a multi-parameter time series from a controlled coastal mesocosm experiment designed to investigate the effects of warming on musselbank communities in the Wadden Sea.
Keywords: abiotic parameters; coastal ecosystem; mesocosm experiment; Sylt